Implementación de un enlace inalámbrico para los bloques administrativos y académicos del centro experimental y producción Salache (ceypsa) de la Universidad Técnica de Cotopaxi - Gustavo Adolfo, Procel Macías (2007)
The present project had like primary target to benefit specially to the technical university of Cotopaxi to the CEYPSA, with end technology as they are the radio networks giving connectivity between two infrastructures as they are the Administrative Block and the Academic Block, thus contributing to the administrative personnel, educational and students to nowadays have movable access to a tool of very important communication as it is the Internet and in addition to give them to greater facility in the communication between users, optimizing human and material resources, improvements in the integrity of the data, greater security to accede to the information, Innovation of the education models learning, labour academic in the CEYPSA, rapidity and cover in the information, use of the space, etc.